Efficacy of mirabegron for ureteral stones: a systematic review with meta-analysis of randomized controlled trials - Wang, Zhenguo; Chi, Junpeng; Liu, Yuhua; Wu, Jitao; Cui, Yuanshan; Yang, Chenchen (Frontiers in Pharmacology, 2023)
Background: Medical expulsive therapy demonstrates efficacy in managing ureteral stones in patients amenable to conservative interventions. This meta-analysis aims to evaluate the effectiveness of mirabegron in the treatment of ureteral stones. Methods:From conception to November 2023, we examined PubMed databases, the Cochrane Library, Embase, Ovid, Scopus, and trials registries for this systematic review and meta-analysis. We chose relevant randomized controlled trials (RCTs) evaluating the efficacy of mirabegron as an expulsive treatment for ureteral stones. The Cochrane risk of bias method was used to assess the quality of the evidence. Outcome measures, which included stone expulsion rate (SER), expulsion time, and pain episodes, were analyzed using RevMan 5.4 and Stata 17. Results: Seven RCTs (N = 701) had enough information and were ultimately included. In patients with ureteral stones, mirabegrontreated patients had a substantially higher SER [odds ratio (OR) = 2.57, 95% confidence interval (CI) = 1.41-4.68, P = 0.002] than placebo-treated ones. Subgroup analysis revealed that mirabegron was superior to placebo in patients with small ureteral stones (OR = 2.26, 95% CI = 1.05-4.87, P = 0.04), with no heterogeneity between studies (P = 0.54; I 2 = 0%). Mirabegron patients had a higher SER than the control group for distal ureteral stones (DUSs) (OR = 2.48, 95% CI = 1.31-4.68, P = 0.005). However, there was no difference in stone ejection time or pain episodes between groups.Mirabegron considerably improves SER in patients with ureteral stones, and the effect appears to be more pronounced for small and DUSs. Nevertheless, mirabegron treatment was not associated with improved stone expulsion time or pain management.